Medical Image Computing and Computer-Assisted Intervention -- MICCAI 2009 12th International Conference, London, UK, September 20-24, 2009, Proceedings, Part II - Yang, Guang-Zhong; Hawkes, David J.; Rueckert, Daniel; Noble, Alison; Taylor, Chris (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2009)
The two-volume set LNCS 5761 and LNCS 5762 constitute the refereed proceedings of the 12th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2009, held in London, UK, in September 2009. Based on rigorous peer reviews, the program committee carefully selected 259 revised papers from 804 submissions for presentation in two volumes. The second volume includes 134 papers divided in topical sections on shape modelling and analysis; motion analyysis, physical based modelling and image reconstruction; neuro, cell and multiscale image analysis; image analysis and computer aided diagnosis; and image segmentation and analysis. .